The many faces of Baltasar da Costa: imitatio and accommodatio in the seventeenth century Madurai mission - Chakravarti,Ananya (2014)
The Jesuit Baltasar da Costa devoted his life to the Madurai mission in seventeenth century Tamil Nadu during the rule of the Nāyaka kings. He was the first Christian missionary to style himself as a paṇṭāram, a Śaiva priest to the lower castes. This paper will argue that his mimetic practice can best be appreciated if read bi-directionally, through the language of European humanism and religious thought, as well as through the new symbolic codes of Nāyaka political order. The article also considers the limits of Costas mimetic practice in terms of its success as an evangelical strategy and in the extent to which it was ultimately predicated upon the maintenance of alterity and not the dissolution of difference.